Приклади інноваційних дослідженнь – 15 років роботи вісника НТУ "ХПІ" - Бухкало, Світлана Іванівна (Національний технічний університет "Харківський політехнічний інститут", 2025)
У матеріалах статті розглянуто приклади визначення цілей навчання студентів університету за освітньою програмою "Готельний та ресторанний менеджмент" та "Хімічна інженерія" з метою розробки складних дисциплін сучасних харчових технологій для складних інноваційних проектів на основі ситуаційних завдань. При написанні статті було використано досвід викладання дисциплін "Загальні технології харчового виробництва", "Харчова хімія", "Процеси та апарати" у 2002–2024 роках. Складні системи визначення складових дисципліни визначили компетентність та якість матеріалу, а розглянуті питання розглядаються крізь призму власного творчого сприйняття, що робить матеріал особливо цінним. Дослідження спрямоване на вивчення таких питань, як: 1) класифікація-ідентифікація моделей організації збору та транспортування відходів; 2) їх класифікація-ідентифікація за методами контролю якості з урахуванням стійкості до дії природних факторів – сонячного світла, води; кліматичних умов та мікроорганізмів; 3) аналіз вибору науково обґрунтованих моделей переробки та утилізації полімерів у складі твердих побутових відходів; 4) розробка необхідних технологічних схем та обладнання для переробки відходів. The materials of the article consider examples of opportunities for determining the goals of training for university students in the educational program Hotel and Restaurant Management and Chemical Engineering in order to develop complex disciplines of modern food technologies for the components of complex innovative projects based on situational tasks. When writing the article, the experience of teaching the disciplines General Food Production Technologies, Food Chemistry, Processes and Devices in 2002–2024 was used. Complex systems for determining the components of the discipline have determined the competence and quality of the material, and the issues considered are overlooked through the prism of one's own creative perception, which makes the material especially valuable. Research is aimed at studying such issues as: 1) classification-identification of models of the organization of waste collection and transportation; 2) their classification-identification according to quality control methods, taking into account resistance to the action of natural factors - sunlight, water; climatic conditions and microorganisms; 3) analysis of the choice of scientifically based models of processing and utilization of polymers as part of solid household waste; 4) development of necessary technological schemes and equipment for waste processing – Bulletin of the National Technical University "KhPI". Series: Innovation researches in students’ scientific work.
Examples innovative research – 15 years bulletin of the NTU "KhPI"
Keywords: хімічна інженерія; готельно-ресторанний бізнес; харчова хімія; інноваційні процеси та технології; ефективні процеси та обладнання; ситуаційні задачі синергетики; chemical engineering; hotel and restaurant business; food chemistry; innovative processes and technologies; effective processes and equipment; situational tasks of synergetic